Metabolic Management during Critical Illness: Glycemic Control in the ICU - Honiden, Shyoko; Inzucchi, Silvio E. (Seminars in Respiratory and Critical Care Medicine, 2015)
Hyperglycemia is a commonly encountered metabolic derangement in the ICU. Important cellular pathways, such as those related to oxidant stress, immunity, and cellular homeostasis, can become deranged with prolonged and uncontrolled hyperglycemia. There is additionally a complex interplay between nutritional status, ambient glucose concentrations, and protein catabolism. While the nuances of glucose management in the ICU have been debated, results from landmark studies support the notion that for most critically ill patients moderate glycemic control is appropriate, as reflected by recent guidelines. Beyond the target population and optimal glucose range, additional factors such as hypoglycemia and glucose variability are important metrics to follow. In this regard, new technologies such as continuous glucose sensors may help alleviate the risks associated with such glucose fluctuations in the ICU. In this review, we will explore the impact of hyperglycemia upon critical cellular pathways and how nutrition provided in the ICU affects blood glucose. Additionally, important clinical trials to date will be summarized. A practical and comprehensive approach to glucose management in the ICU will be outlined, touching upon important issues such as glucose variability, target population, and hypoglycemia.
Keywords: hyperglycemia; hypoglycemia; critical illness; glycemic control; insulin resistance